Design of multifunctional interfaces on ceramic solid electrolytes for high-performance lithium-air batteries - Yunxin Shi; Ziyang Guo; Changhong Wang; Mingze Gao; Xiaoting Lin; Hui Duan; Yonggang Wang; Xueliang Sun (Green Energy & Environment)
High-energy-density lithium (Li)–air cells have been considered a promising energy-storage system, but the liquid electrolyte-related safety and side-reaction problems seriously hinder their development. To address these above issues, solid-state Li–air batteries have been widely developed. However, many commonly-used solid electrolytes generally face huge interface impedance in Li–air cells and also show poor stability towards ambient air/Li electrodes. Herein, we fabricate a differentiating surface-regulated ceramic-based composite electrolyte (DSCCE) by constructing disparately LiI-containing polymethyl methacrylate (PMMA) coating and Poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) layer on both sides of Li1.5Al0.5Ge1.5(PO4)3 (LAGP). The cathode-friendly LiI/PMMA layer displays excellent stability towards superoxide intermediates and also greatly reduces the decomposition voltage of discharge products in Li–air system. Additionally, the anode-friendly PVDF-HFP coating shows low-resistance properties towards anodes. Moreover, Li dendrite/passivation derived from liquid electrolyte-induced side reactions and air/I-attacking can be obviously suppressed by the uniform and compact composite framework. As a result, the DSCCE-based Li–air batteries possess high capacity/low voltage polarization (11,836 mA h g−1/1.45 V under 500 mA g−1), good rate performance (capacity ratio under 1000 mA g−1/250 mA g−1 is 68.2%) and long-term stable cell operation (∼300 cycles at 750 mA g−1 with 750 mAh g−1) in ambient air.